Can a patient’s death go unpunished? Mediation with the deceased patient’s family in criminal cases involving a medical error - Bek, Dominika; Hanc, Jakub (Medicine, Law & Society, 2021)
A medical error resulting in a patient’s death is one of the most difficult experiences in the professional practice of medical personnel. A healthcare professional faces the suffering and grievances of the deceased patient's relatives and, at the same time, the prospect of legal liability including a criminal penalty and prohibition from practising a profession. This article attempts to address the issue of the necessity and usefulness of applying such far-reaching consequences in all cases of the patient's death caused through a fault attributable to a healthcare professional. It argues for the widest possible use of mediation in cases of medical error, in particular in criminal law cases. It focuses on reasonable expectations of the deceased patient’s family and the need for the improvement of standards of health protection in similar cases. This perspective makes it possible to conclude that a criminal penalty for the perpetrator of an error is not always in the public interest.As regards the possibility of using mediation in cases involving a medical error, this article refers to the Polish normative tradition, although the dilemma highlighted in its title is certainly of a universal and transnational nature.